Long-term changes of salivary exoglycosidases and their applicability as chronic alcohol-drinking and dependence markers. (2nd January 2019) - Waszkiewicz, Napoleon; Kratz, Ewa Maria; Chojnowska, Sylwia; Zalewska, Anna; Zwierz, Krzysztof; Szulc, Agata; Szajda, Sławomir Dariusz; Nestsiarovich, Anastasiya; Kapitau, Andrei; Kępka, Alina; Ostrowska, Lucyna; Ferens-Sieczkowska, Mirosława
Abstract: Objectives: Investigation of long-term dynamic changes of salivary activity/output of exoglycosidases, deglycosylation processes and their applicability as alcohol markers. Methods: Exoglycosidase (α-fucosidase (FUC), β-galactosidase (GAL), β-glucuronidase (GLU), β-hexosaminidase (HEX, HEX A and HEX B isoenzymes) and α-mannosidase (MAN)) activities were measured in the saliva of healthy social drinking controls (C), alcohol-dependent non-smokers (ANS) and alcohol-dependent smokers (AS) at the 1st, 15th, 30th and 50th day of abstinence after chronic alcohol drinking. Results: The activity of exoglycosidases was 2–3-fold (MAN), 2–6 fold (FUC), 8–25-fold (HEX A) and 19–40-fold (GLU) higher in the ANS and AS groups than in controls, and had good/excellent sensitivity, specificity and accuracy. The higher outputs of exoglycosidases were in the AS and ANS groups than in controls at the 1st day (GLU, HEX A) and at the 50th day (GLU, FUC, MAN) of abstinence. We found numerous correlations between alcohol-drinking days with GLU and HEX A, alcohol amounts with HEX A and duration of alcohol dependence with FUC and MAN activity/output. Conclusions: Salivary exoglycosidases/deglycosylation processes were still very high up to 50 days after the end of alcohol consumption. We found markers of chronic alcohol consumption (HEX A), alcohol dependence (FUC and MAN) and chronic alcohol consumption and dependence (GLU).